Tweeting the meeting: Quantitative and qualitative twitter activity during the 38th ESSO conference. Issue 2 (February 2019) - Søreide, Kjetil; Mackenzie, Graham; Polom, Karol; Lorenzon, Laura; Mohan, Helen; Mayol, Julio
Abstract: Introduction: Social media is increasingly used to share information with the potential for fast and wide reach. Data on use during surgical oncology conferences is limited. We aimed to monitor twitter usage during a surgical oncology conference to audit impact of activity. Methods: A prospective, time-restricted, observational study of twitter activity using the #ESSO38 hashtag in the week before and during the 38th ESSO conference (10–12 October 2018; Budapest, Hungary). Data on individual tweets and retweets, including date and tweeter or retweeter were collected using NodeXL, FollowTheHashtag, Twitonomy and TAGS. Results: The study period (10–13 October) documented 328 tweets by 58 tweeters with 1167 retweets, with a soaring activity and mentions during the conference days, with a potential reach at over 7.5 million. The nodal network of tweets, the most active tweeters and retweeters are presented as well as the most frequently used hashtags. The top 3 hashtags used were #ESSO38, #SoMe4Surgery# and #EYSAC. A positive influence on the @ESSOweb twitter handle was noted, with the numbers of followers growing from 1.5 K to over 1.8 K representing a 20% growth in just over a week. Conclusions: Activity on tweeter during the conference was considerable, with a potential for a wide reach beyond those attending the conference. A more structured approach to the use of twitter for future conferences may enhance experience, activity and reach.